1993
DOI: 10.1007/bf00154226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic vanadium administration in drinking water to rats

Abstract: Two-month old Wistar rats of both sexes received, as sole drinking liquid, an aqueous solution of ammonium metavanadate (AMV) at a concentration of 0.01 or 0.05 mg V cm-3 (0.2 or 1.0 mM) for a period of 4 weeks. It was calculated that the animals took up doses of 1.5 and 5-6 mg V kg body weight-1 24 h-1, respectively. Food and AMV solution consumption in the experimental group was similar to food and water consumption in the control group. A statistically significant decrease of consumption of AMV solution at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 35 publications
3
10
2
1
Order By: Relevance
“…The unchanged L-ascorbic acid concentration in RBCs between the control and SMV-only treated rats shown in the present experiment (Table 6) was also observed in our previous studies after ammonium metavanadate (AMV) intoxication (Zaporowska et al 1993(Zaporowska et al , 1997. The plasma L-ascorbic acid content did not change either; however, in our earlier studies, its significant decrease in the plasma following vanadate treatment in drinking water was found (Zaporowska et al 1997;Ścibior and Zaporowska 1998;Ścibior 1999).…”
Section: Interactive Effect Of V and Cr A Ns Nssupporting
confidence: 90%
See 2 more Smart Citations
“…The unchanged L-ascorbic acid concentration in RBCs between the control and SMV-only treated rats shown in the present experiment (Table 6) was also observed in our previous studies after ammonium metavanadate (AMV) intoxication (Zaporowska et al 1993(Zaporowska et al , 1997. The plasma L-ascorbic acid content did not change either; however, in our earlier studies, its significant decrease in the plasma following vanadate treatment in drinking water was found (Zaporowska et al 1997;Ścibior and Zaporowska 1998;Ścibior 1999).…”
Section: Interactive Effect Of V and Cr A Ns Nssupporting
confidence: 90%
“…However, the results of our study showed that V (as SMV), at the dose of 9 mg V/kg b.w./24 h, ingested by rats in drinking water during 12 weeks, did not have a prooxidant effect on RBCs, which was reflected in the unchanged L-ascorbic acid concentration and MDA level as well as Cu,Zn-SOD, CAT, cGSH-Px, and GR activities in these cells (Tables 6,7,and 8). The unaltered SOD activity in RBCs after treating the rats vanadate in drinking water was also demonstrated in our previous study (Ścibior 1999) and in the studies of Sekar et al (1990), Oster et al (1993) and Russanov et al (1994); whereas the unchanged erythrocyte CAT activity after vanadate intoxication was shown by Sekar et al (1990), Zaporowska et al (1993) and by Russanov et al (1994). The unaltered erythrocyte cGSH-Px activity found in the present experiment was also demonstrated in the studies of Russanov et al (1994) and in our earlier study (Ścibior 1999), but contradictory results showing increased activity (Tas et al 2006) have been reported, too.…”
Section: Interactive Effect Of V and Cr A Ns Nssupporting
confidence: 80%
See 1 more Smart Citation
“…The erythrocyte count was significantly decreased at both dose levels associated with a significant decrease of the haemoglobin level and increased percentage of reticulocytes in the peripheral blood at the highest dose level. In addition, the L-ascorbic acid level in the plasma of males was significantly decreased at both dose levels (Zaporowska et al, 1993).…”
Section: Subacute/subchronic Toxicitymentioning
confidence: 90%
“…Several studies have shown that vanadium exposure may cause respiratory dysfunction, 10 hematologic and biochemical alterations, renal toxicity, 11 reproductive and developmental toxicity immunotoxicity, mutagenicity, 12 and neurotoxicity may also occur 13 when readily exposed. In some instances, the cases of death due to exposure to vanadium compounds has also been reported.…”
Section: Vanadium Toxicitymentioning
confidence: 99%